2016
DOI: 10.1080/21551197.2016.1206762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Ginger Supplementation on Proinflammatory Cytokines in Older Patients with Osteoarthritis: Outcomes of a Randomized Controlled Clinical Trial

Abstract: There is limited evidence that ginger powder consumption can relieve pain and inflammation due to specific anti-inflammatory phytochemical constitutents. This study investigates the effect of ginger supplementation on proinflammatory factors in participants (n = 120) of a randomized double-blind placebo-controlled 3-month clinical trial investigating knee osteoarthritis. Patients were randomly assigned to one of two groups: the ginger group (GG) or the placebo group (PG). Administered daily for 3 months, parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(59 citation statements)
references
References 24 publications
2
53
0
4
Order By: Relevance
“…All studies reported improvement following ginger intake compared to the control group. For instance, Mozaffari-Khosravi et al proposed that benefits of ginger were observed due to a reduction in the level of the proinflammatory cytokines after three months of consuming 500 mg of ginger powder [13]. Other studies showed a promising benefit of ginger in relieving pain in OA patients.…”
Section: Inflammatory Effectmentioning
confidence: 99%
See 1 more Smart Citation
“…All studies reported improvement following ginger intake compared to the control group. For instance, Mozaffari-Khosravi et al proposed that benefits of ginger were observed due to a reduction in the level of the proinflammatory cytokines after three months of consuming 500 mg of ginger powder [13]. Other studies showed a promising benefit of ginger in relieving pain in OA patients.…”
Section: Inflammatory Effectmentioning
confidence: 99%
“…Another SR-MA study revealed that ginger improved lipid profiles and benefited the glucose control, insulin sensitivity, and glycosylated hemoglobin of type 2 diabetes mellitus [12]. In addition, ginger's potency has been regularly proposed in arthritis, gastric dysfunction, and cancers [6,13,14].…”
Section: Introductionmentioning
confidence: 99%
“…A clinical trial evaluated the effect of ginger supplementation in older patients with osteoarthritis. This trial show a reduction in inflammatory markers like TNF-α and IL-1β [13]. In addition, another trial reported a reduction in nitric oxide and hs-CRP levels in ginger-supplemented osteoarthritis patients compared to the control group [14].…”
Section: Introductionmentioning
confidence: 71%
“…The sample size was calculated according to primary outcomes (if data were available), and the maximum calculated sample size was considered. The sample size was based on the changes observed in the TNF-α in the study by Mozafari Khosravi [13] as a result of ginger supplementation. Considering a type I error of 0.05, a test power of 90%, and follow-up loss of 10%, the sample size required in each group was calculated to be 22 patients.…”
Section: Sample Sizementioning
confidence: 99%
“…В рандомизированном клиническом исследовании с участием 49 пациентов с ОА коленных суставов, которые принимали метилсульфонилметан в течение 12 нед, показано уменьшение боли и улучшение физических функций [22]. Установлено благоприятное действие веществ растительного происхождения при ОА [23]: противовоспалительное -у имбиря (снижение сывороточных уровней фактора некроза опухоли α, интерлейкина 1β) [24] и анальгетическое -у окопника [25], а также способность ингибировать транскрипционные факторы AP-1, NF-κB и модифицировать активность матриксных ММП 1 и 13 [26].…”
unclassified